Cults and rites in Ancient Greece essays on religion and society - Jameson, Michael H. 1924-2004 (Cambridge University Press, 2014)
This volume assembles fourteen highly influential articles written by Michael H. Jameson over a period of nearly fifty years, edited and updated by the author himself. They represent both the scope and the signature style of Jameson's engagement with the subject of ancient Greek religion. The collection complements the original publications in two ways: firstly, it makes the articles more accessible; and secondly, the volume offers readers a unique opportunity to observe that over almost five decades of scholarship Jameson developed a distinctive method, a signature style, a particular perspective, a way of looking that could perhaps be fittingly called a 'Jamesonian approach' to the study of Greek religion. This approach, recognizable in each article individually, becomes unmistakable through the concentration of papers collected here. The particulars of the Jamesonian approach are insightfully discussed in the five introductory essays written for this volume by leading world authorities on polis religion